Basic symptoms of schizophrenia are related to symptoms of traumatic stress: A pivotal role of sensitization. An observational study. Issue 28 (15th July 2022) - Pec, Ondrej; Lysaker, Paul H.; Bob, Petr
Abstract : Introduction: Subjective cognitive deficits have been broadly reported in schizophrenia and described by Huber as basic symptoms. It remains unclear however to what extent they may be related to psychosocial stressors including trauma. Methods: We assessed basic symptoms using the Frankfurt Complaint Questionnaire (FCQ) in a sample of 40 patients with schizophrenia. Trauma-related symptoms were assessed concurrently using the Trauma Symptom Checklist-40, symptoms of dissociation using the Dissociative Experiences Scale, and sensitization phenomena using the Complex Partial Seizure-like Symptoms Inventory and Limbic System Checklist-33. Psychotic symptoms were measured by Health of the Nation Outcome Scales. The dosage of antipsychotic medication was assessed in terms of equivalents of chlorpromazine, and antidepressant medication in terms of equivalents of fluoxetine. Spearman correlations were performed to explore the relationship between FCQ and other trauma-related measures. To determine the relative contributions of trauma-related symptoms to basic symptoms a linear regression analysis was performed. Results: The results showed that higher levels of basic symptoms of schizophrenia were associated with greater levels of symptoms of dissociation, traumatic stress, and sensitization or kindling-like processes in schizophrenia. Among the trauma-related variables, sensitization phenomena assessed with Complex Partial Seizure-like Symptoms Inventory were closely associated with basic symptoms. Discussion: These results indicate that basic symptoms measured by FCQ might be related to trauma. The potential of trauma to influence neurodevelopmental hypotheses of schizophrenia is discussed.